Philosophy underlying emotional intelligence in relation to level of curiosity and academic achievement of rural area students - Hassan, Aminuddin; Sulaiman, Tajularipin; Ishak, Rohaizan (Science Publications, 2009)
Problem statement: Since emotional intelligence is still not wholly-accepted despite evidences of its powerful influence in general setting, this study is therefore conducted to identify the emotional intelligence level among school students in rural areas, relationships between emotional intelligence and anxiety, as well as relationships between emotional intelligence and academic achievement. Approach: It involved a sample of 223 form 1 and form 4 students. Process of data collection was administered by using a set of questionnaire which includes a self report measure of emotional intelligence adapted from Schutte Self-Report of Emotional Intelligence (SSRI) and Beck Anxiety Inventory (BAI). T-test analysis showed that there were no significant differences for the emotional intelligence level within all students between ages 13 and 16. However, there were significant differences for the emotional intelligence level among female students in accordance to age. Results: The results showed that there were significant differences for emotional intelligence level among all students between both genders. Mean score of emotional intelligence within female students appeared to be higher than male students. Pearson correlation analysis showed that emotional intelligence levels of all students were significant negatively in relation to anxiety level. Emotional intelligence was also significant positively in correlation with academic achievement of all variables including students’ age and gender. Conclusion: Besides emotional intelligence, the study revealed that anxiety was also significantly correlated in a negative manner with academic achievement among all students.